ANALISA PEMINDAHAN IBUKOTA NEGARA - Wesley Liano Hutasoit (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2019)
Jakarta has been designated as the capital of the state through the Law of the Republic of Indonesia Number 10 of 1964 On Statement of the Special Capital Region of Jakarta Raya Staying as the Capital of the Republic of Indonesia By the name of Jakarta, it is also the center of government and the business center that transforms it has the appeal for the population to Live and earn a living in the capital. Indonesia moved the capital to Yogyakarta from January 1946 to December 1949 because of the war of independence. From Bukittinggi in West Sumatra it was also a capital city when President Sukarno formed an emergency government before he was captured by the Dutch between December 1948 and June 1949. Bireuen in Aceh Province had also been the capital of the country for only a week, and after that the capital returned to Jakarta awaits independence through the Proclamation of Independence of the Unitary State of the Republic of Indonesia. The move of the nation's capitals takes place in several countries and some countries have success stories in their efforts to move the old capital to new places, such as Kuala Lumpur to Putrajaya in Malaysia, Bonn to Berlin in Germany, Melbourne to Canberra in Australia, Valladolid to Madrid in Spain, or Kyoto to Tokyo in Japan. Successful capital relocation can occur in both developed and developing countries. Dubai is known worldwide as a key business city but Abu Dhabi is the capital of the United Arab Emirates. In India, Mumbai is the business capital, while New Delhi is the seat of government. Common reasons for the transfer of the capital are socio-economic considerations, political considerations, and geographical considerations. Indonesia considers all three factors in the analysis to move its capital, not only in-country analysis, but also an analysis of the experiences of other countries in the world that have moved their capital. The experience of the various countries that have moved their capital will provide input and consideration that would otherwise be used as a more appropriate analytical tool to examine problems in Indonesia.